Characterisation of airway disease associated with Sjögren disease - Eric Hachulla; Xavier Mariette; Jacques-Eric Gottenberg; Marie-Pierre Debray; Philippe Dieude; Alain Saraux; Olivier Vittecoq; Emanuelle Dernis; Raphaele Seror; Gaetane Nocturne; Cindy Marques; Veronique Le Guern; et al. (RMD Open)
Objective Although airway disease associated with Sjögren’s disease (Sjo-AD) is common, it is poorly studied compared with interstitial lung disease (ILD). In this study, we aimed to assess factors associated with Sjo-AD, the characteristics and prognosis of this manifestation.Methods We performed a retrospective multicentric study involving nine centres. We included Sjo-AD patients confirmed by at least one clinician and one CT scan report. Clinical and biological data, pulmonary function test (PFT), and CT scans were collected. A single radiologist specialist in thoracic diseases reviewed CT scans. Sjo-AD patients were compared with Sjo controls without pulmonary involvement, randomly selected after matching for age and disease duration.Results We included 31 Sjo-AD and 62 Sjo controls without pulmonary history. Sjo-AD had a higher disease activity (ESSDAI) compared with controls, even when excluding the pulmonary domain of the score (7 vs 3.8, p<0.05), mainly due to the biological activity. Sjo-AD was multilobar (72%) and associated with signs of both bronchiectasis and bronchiolitis (60%). Obstructive lung disease occurred in 32% at the time of Sjo-AD diagnosis. Overall, PFT was stable after 8.7±7 years follow-up but repeated CT scans showed extended lesions in 41% of cases within 6±3.2 years. No patient developed Sjo-ILD. Sjo-AD progression was independent of the global disease activity.Conclusions Sjo-AD preferentially affects Sjo patients with higher biological activity. It is often characterised as a diffuse disease, affecting both proximal and distal airways, with a slow evolution over time and no progression to Sjo-ILD.